The use of molecularly imprinted polymers for the multicomponent determination of endocrine-disrupting compounds in water and sediment - Matějíček, David; Grycová, Alena; Vlček, Jiří (Journal of separation science, 2013)
The method employing molecularly imprinted polymers for the extraction and clean up of endocrine-disrupting compounds (estrogens, bisphenol A, and alkylphenols) from water and sediment is described. The identical extraction/clean-up and LC-MS/MS condition were used for the analysis of both types of samples. The method showed high recoveries ranging from 90 to 99% with excellent precision (intrabatch: 3.6-9.3%; interbatch: 5.6-11.4% for water; intrabatch: 4.3-8.5%; interbatch: 6.1-9.6% for sediment). The LOD was in the range of 0.7-1.9 ng/L and 0.3-0.6 ng/g for water and sediment, respectively. Overall extraction on molecularly imprinted polymers substantially enhanced sample clean-up. The difference in efficiency of clean-up was particularly pronounced when a large sample volume/weight was extracted and analyzed. Finally, the method was successfully applied for the analysis of 20 water and sediment samples.
Keywords: polymery; extrakce na pevné fázi; Endocrine Disruptors; vysokoúčinná kapalinová chromatografie; endokrinní disruptory; Geologic Sediments; Solid Phase Extraction; geologické sedimenty; Polymers; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; chemické látky znečišťující vodu; Water Pollutants, Chemical; molekulový imprinting; Molecular Imprinting; Tandem Mass Spectrometry